Hysteretic behavior of bolt–column joints under in-plane loading combinations by experimental and numerical study. (1st June 2020) - Ma, H.H.; Ma, Y.Y.; Yu, Z.W.; Jiang, P.; Fan, F.; Meng, Z.P.
Highlights: The hysteretic behavior of BC joints under bending and axial forces is investigated. A series of tests were conducted on the bending behavior of the joints. The joint hysteretic loop under in-plane bending pinches significantly. Appropriate axial pressure can improve the hysteretic behavior of the joints. Hysteretic capacity of the joint under My is weaker than that of the joint under Mx . Bearing capacity of the joint under Mx is weaker than that of the joint under My . Abstract: The bolt–column (BC) joint has enough bending stiffness satisfying large-span single-layer reticulated shell structure well. The hysteretic behavior of BC joints under different in-plane combinations of bending moment and axial force is investigated in this study. Firstly, precise finite element models (FEM) of the BC joints, which considered the material and the geometric and contact nonlinearities, were established in ABAQUS. The failure modes, hysteretic curves, skeleton curves, and bearing capacity for assessing the joint hysteretic behavior were investigated in detail by the numerical analysis. BC joints under different combined axial force and cyclic bending loads were studied by numerical analysis to obtain the impact of the axial force, which provides necessary technical support for engineering practice. Three tests were conducted and the results verified that the FEM was effective in simulating the joint behavior by comparison with the test results. The research shows that the hysteretic capacity of BC joints under in-plane bending is weaker than that under out-of-plane bending, but the bearing capacity of former is higher. Increasing the thickness of the side and middle plates can slightly enhance the joint in-plane hysteretic capacity, which is improved with small axial compression and reduced with high axial compression and axial tension.